2009
DOI: 10.1007/s10006-009-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic involvement of parotid from carcinoma of the breast—a case report

Abstract: Microscopic examination of parotid and breast revealed that parotid gland was involved as a distant metastases from a breast carcinoma, indicating that a swelling in the parotid needs to be assessed and investigated very carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…[6,7] On the other hand, parotid metastatic disease originating from distant infraclavicular sites is rare; tumor cells from such sites are thought to reach the parotid gland through the thoracic duct or the paraspinal venous plexus. [8] The majority of parotid metastasis from breast cancer reported in the literature originate from invasive ductal carcinoma. [9] In 2000, Joyce et al reported the first documented case of breast cancer metastasizing to the parotid gland in a male patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] On the other hand, parotid metastatic disease originating from distant infraclavicular sites is rare; tumor cells from such sites are thought to reach the parotid gland through the thoracic duct or the paraspinal venous plexus. [8] The majority of parotid metastasis from breast cancer reported in the literature originate from invasive ductal carcinoma. [9] In 2000, Joyce et al reported the first documented case of breast cancer metastasizing to the parotid gland in a male patient.…”
Section: Discussionmentioning
confidence: 99%
“…For example, primary salivary duct carcinoma mainly affects elderly men, and its occurrence as a metachronous or synchronous tumor with ductal carcinoma of the breast is unlikely and rarely described in the literature. [8] When metastatic carcinoma is identified by parotid FNA biopsy, restaging with [18F]-fluorodeoxyglucose positron emission tomography-CT scan is recommended to evaluate locoregional and look for distant disease. [16] Treatment planning is then based on radiological staging.…”
Section: Discussionmentioning
confidence: 99%
“…Distant spread through the lymphatic route occurs to the mediastinal and supraclavicular lymph nodes. Also hematogenous spread occurs and leads to metastasis to lung, liver, bone, adrenals, and brain [10]. How- adjuvant chemotherapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic parotid gland involvement accounts for approximately 9-14% of all parotid tumors [1]. Metastasis to the parotid gland from breast cancer is extremely rare, and to our knowledge only 14 cases have been reported between 1982 and 2010 [2][3][4][5][6][7][8][9][10]. We report a case of invasive lobular carcinoma of the breast which spread to the parotid gland, and we summarize the 14 cases that have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation